The discursive construction of resistance to sex in an online community. (August 2020) - Wright, David
Abstract: This paper reports the analysis of a 26-million-word corpus of data from an online Pick-Up Artist (PUA) discussion forum. PUAs often use discussion forums as a place to share 'field reports' of their experiences in seducing and sleeping with women. Such online environments therefore provide a unique communicative space in which the notion of resistance to sex is discursively constructed and represented by forum members. Research in forensic linguistics has traditionally focused on the ways in which discourses of 'resistance' are used by police and lawyers to determine whether consent was given in cases of rape and sexual assault. This paper, therefore, provides an alternative perspective to this issue, and applies a corpus-assisted approach to discourse analysis in order to identify the ways in which 'resistance' is represented by this part of the PUA community. A collocation analysis of the community-specialist term 'LMR' ('Last Minute Resistance') finds three major themes emerging from the data: (i) resistance as something to be overcome, (ii) resistance as insincere, and (iii) resistance as remarkable. The paper ends with a discussion of the implications of these findings, namely in terms of counter-balancing the utmost resistance standard in the legal system and providing education to prevent the incitement of sexual aggression and cyber-enabled violent offences against women and girls.